Evaluation of the effect of respiratory disease protection educationgiventoadolescents in Kemalpasa Turkiye - Bilgic, Nurcan; Mermer, Gulengul (Journal of the Pakistan Medical Association, 2026)
Objective: To evaluate the effectiveness of education given to adolescentsabout protection against respiratory-transmitted diseases. Method: Thequasi-experimental, multi-phase study was conducted from October 1, 2020, to June 11, 2021, at a vocational and technical high school in Anatolia, Turkiye, after approval from the ethics review committee ofEge University, Turkiye, and comprised students of either gender in grades 9, 10, 11, and 12in the 2020-2021 academic year. Data wascollected during face-to-face interviewsthroughthe Student Information Formand the Scale for Assessing Perceptions and Attitudes Towards the Coronavirus Disease-2019 Outbreak. Educational material and video films of the Ministry of Health were edited and used during the educationphase. To evaluate the effectiveness of the education, the students’ level of knowledge about protection from respiratory-transmitted diseaseswas tested again 3 months after the education intervention. Baseline and post-intervention leveks were compared to assess the impact of the intervention. Data was analysed using SPSS 26. Results: Of the 665 students, 302(45.4%) participated in the pre-test, while 374(56.2%) attended the education phase, and 365(54.9%) participated in the post-test. The open-ended question in the post-test was answered by 310(84.9%) subjects. The majority of the students were male 284(94.0%), and aged 13-16 years 283 (93.8%). The statement "Respiratory diseases are caused by bacteria" was correctly affirmed by 236(78.1%) of the students before and 278(76.2%) after the education. There was a significant difference between the awareness of the students post-intervention compared to baseline about the transmission route of the infectious agent, the disease process, and the importance of wearing a mask. The difference was also significant in terms of students’ perception of danger, contagiousness, causes, conspiracy, environment, macro, avoidance behaviors, cognitive avoidance, avoidance of common areas, and avoidance of personal contact (p<0.05). Conclusion: Continuous education of adolescents, families and teachers within the scope of school health contributed to the prevention of respiratory diseases and health promotion. Key Words: Adolescent, Respiratory tract diseases, Educational assessment, Public health, Nursing.